ANALISIS PERKEMBANGAN EFISIENSI TEKNIS BANKSYARIAHDI INDONESIA DENGAN METODE DATAENVELOPMENT ANALYSIS (DEA) TAHUN 2005-2009 - Muhammad Biwa Nugraha (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2011)
Economic development of a country, requires a well planned and directedprogram and also requires a sufficient capital or development found. Therefore,Banking will be required as the financial institution and as the center ofdevelopment. The government has implemented several improvement towards theperformance of Banking by establising several policies. One of those policies is,Banks is free to determine their own interest rate. Which that policy sah motivatesthe development of establishment of Syariah Banks which its basis is on the profitsharing and not on the interest rate.The rapid development of the Syariah Bankingwhether perceiency improvement of the Syariah Bank it self. In this research, the writer was attemted to observe the efficiency rate of theeconomic activities unit (UKE) of Syariah Bank. Data was used here is the Inputsecondary data and Output on the period of 2005-2009. Input could be classifiedinto the general expense and administration, personnel expense, operations expense.Mean while, the output is operational income, and income from lending. The result of this research showed that, the efficiency rate of 4 UKEs (BankSyariahMandiri, Bank Mega Syariah, Bank MuamalatSyariah, dan Bank BukopinSyariah) that was examined, During 2005-2009, there is only one Islamic bank canmaintain a constant level of maximum efficiency of 100% is Bank SyariahMandiri.Keyword: Efficiency, DEA